2009
DOI: 10.1002/nur.20363
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term in‐home intervention reduces depressive symptoms in Early Head Start Latina mothers of infants and toddlers

Abstract: Depressive symptoms may compromise the ability of low-income Latina mothers with limited English language proficiency to parent their infants or toddlers. Eighty Early Head Start Latina mothers with limited English language proficiency were randomized to an advanced practice nurse-delivered, culturally tailored, in-home psychotherapy intervention, or to usual care. Repeated measures regression analysis showed a significantly greater decrease in depressive symptoms for intervention mothers compared to the usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 91 publications
3
100
2
3
Order By: Relevance
“…This percentage is greater than others have reported (Beeber et al, 2010; Campbell, Matestic, von Stauffenberg, Mohan, & Kirchner, 2007; Edwards et al, 2012; Riola, Nguyen, Greden, & King, 2005) and may be due to more frequent assessments over the initial 6 month postpartum period. This high proportion having depressive symptoms may also indicate that the first 6 months is indeed a critical period of adaptation as others have speculated (Goodman, 2009).…”
Section: Discussioncontrasting
confidence: 68%
“…This percentage is greater than others have reported (Beeber et al, 2010; Campbell, Matestic, von Stauffenberg, Mohan, & Kirchner, 2007; Edwards et al, 2012; Riola, Nguyen, Greden, & King, 2005) and may be due to more frequent assessments over the initial 6 month postpartum period. This high proportion having depressive symptoms may also indicate that the first 6 months is indeed a critical period of adaptation as others have speculated (Goodman, 2009).…”
Section: Discussioncontrasting
confidence: 68%
“…All of the measures used in the study had excellent reported reliability and validity indices with low-literacy populations; most had been used in previous studies in this population by the research team (Beeber et al, 2004; Beeber et al, 2010). In addition, measurement techniques used in previous clinical trials of in-home interventions were improved upon.…”
Section: Methodsmentioning
confidence: 99%
“…In the acute postpartum period, there exists a substantial literature for evidence-based psychological interventions for treating PPD, such as interpersonal psychotherapy (Stuart S & O'Hara, 1995; Grote et al, 2009; Zlotnick, Miller, Pearlstein, Howard, & Sweeney, 2006; Beeber et al, 2010; Brandon et al, 2012; Beeber et al, 2013), cognitive behavioral therapy (Cooper, Murray, Wilson & Romaniuk, 2013) and group psychoeducation (Honey, Bennett & Morgan, 2002; Morgan, Matthey, Barnett & Richardson, 1997). Mothers with moderate to severe depressive symptoms should be treated with pharmacotherapy as an appropriate first line and efficacious intervention (Yonkers et al, 2011; Einarson, 2010).…”
Section: Intervention: Mental Health and Early Intervention Servicesmentioning
confidence: 99%